Icaritin Derivative IC2 Induces Cytoprotective Autophagy of Breast Cancer Cells via SCD1 Inhibition - Yi-Xuan Wang; Yi-Yuan Jin; Jie Wang; Zi-Cheng Zhao; Ke-Wen Xue; He Xiong; Hui-Lian Che; Yun-Jun Ge; Guo-Sheng Wu (Molecules, 2023)
Breast cancer is one of the most prevalent malignancies and the leading cause of cancer-associated mortality in China. Icaritin (ICT), a prenyl flavonoid derived from the Epimedium Genus, has been proven to inhibit the proliferation and stemness of breast cancer cells. Our previous study demonstrated that IC2, a derivative of ICT, could induce breast cancer cell apoptosis by Stearoyl-CoA desaturase 1 (SCD1) inhibition. The present study further investigated the mechanism of the inhibitory effects of IC2 on breast cancer cells in vitro and in vivo. Our results proved that IC2 could stimulate autophagy in breast cancer cells with the activation of adenosine monophosphate (AMP)-activated protein kinase (AMPK) signaling and mitogen-activated protein kinase (MAPK) signaling. Combination treatment of the AMPK inhibitor decreased IC2-induced autophagy while it markedly enhanced IC2-induced apoptosis. In common with IC2-induced apoptosis, SCD1 overexpression or the addition of exogenous oleic acid (OA) could also alleviate IC2-induced autophagy. In vivo assays additionally demonstrated that IC2 treatment markedly inhibited tumor growth in a mouse breast cancer xenograft model. Overall, our study was the first to demonstrate that IC2 induced cytoprotective autophagy by SCD1 inhibition in breast cancer cells and that the autophagy inhibitor markedly enhanced the anticancer activity of IC2. Therefore, IC2 was a potential candidate compound in combination therapy for breast cancer.